2001
DOI: 10.1136/adc.84.3.218
|View full text |Cite
|
Sign up to set email alerts
|

Social class difference in catch up growth in a national British cohort

Abstract: Aim-To examine the influence of socioeconomic status on growth pattern in height from age 7 to 23 years. Methods-Prospective cohort study. A total of 10 200 white singleton born children from the 1958 British birth cohort (National Child Development Study) were analysed. Results-DiVerences in height by birth weight persisted throughout the follow up period. However, the mean diVerences in height between low birth weight infants (<2500 g) and adequate birth weight infants (>2500 g) were less notable in social c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…Indeed, early life disadvantage such as low birth weight is more effectively overcome by those in each successively higher social strata. 21 Conspicuously missing from all studies is consideration of the social context. The findings reported in this paper concerning gradients in characteristics related to subsequent health underscore the need for consideration of context, including not only social context but also material context, including access to food markets with affordable nutritious foods and access to safe facilities for physical exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, early life disadvantage such as low birth weight is more effectively overcome by those in each successively higher social strata. 21 Conspicuously missing from all studies is consideration of the social context. The findings reported in this paper concerning gradients in characteristics related to subsequent health underscore the need for consideration of context, including not only social context but also material context, including access to food markets with affordable nutritious foods and access to safe facilities for physical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…20 Interestingly, the height deficit of low birthweight infants was smaller in the higher social class groups when children were assessed at 7, 11, 16, and 23 years of age. 21 By the age of 16, the deficits of higher social class adolescents were no longer significantly different from that of their normal birthweight peers.…”
Section: Morbidity and Health Statusmentioning
confidence: 97%
“…Social conditions during childhood may be an important determinant of achieving catch up growth and the persistence of undernutrition into later years. 25 Thus, while social class gradients in intrauterine growth are well known, 21 26 whether social deprivation has a more persistent effect on nutritional status during childhood is unclear. Evidence on social inequalities in childhood under and overnutrition is therefore lacking.…”
mentioning
confidence: 99%
“…Studies using parents' occupation and education level as criteria have identified that children of professionals or salaried employees with a high education level are taller than those whose parents are unqualified workers. This is associated with lower education level and has been documented in Sweden (Nystrôm-Peck & Vagero, 1987;Heineck, 2006), Germany (Kromeyer et al, 1997;Heineck, 2006) and England (Teranishi et al, 2001). In a recent study in Mexico, significant height differences were documented between the children of women with basic (elementary and junior high school) and university education levels (Moguel Canul, 2011).…”
Section: Introductionmentioning
confidence: 85%
“…Among the criteria commonly used to classify individuals into social classes are parents' occupation, employment and education levels (Nystrôm-Peck & Vagero, 1987;Kromeyer et al, 1997;Teranishi et al, 2001;Heineck, 2006), family or head of household income (Silventoinen et al, 1999) and place of residence (rural or urban zone) (Silventoinen et al, 1999;Komlos & Kriwy, 2003). Studies using parents' occupation and education level as criteria have identified that children of professionals or salaried employees with a high education level are taller than those whose parents are unqualified workers.…”
Section: Introductionmentioning
confidence: 99%